Development of Online Laboratories for Modulation and Combinational Logic Circuit Analysis Using NI ELVIS IITM Platform - Mwikirize, Cosmas; Tumusiime Asiimwe, Arthur; Musasizi, Lea; Namuswa, Victoria; Nakasozi, Mary Dawn; Mugga, Charles; Katumba, Andrew; Tickodri - Togboa, Sandy Stevens; Butime, Julius; Musasizi, Paul Isaac (New Generations, 2010)
This paper describes the work carried out by the Makerere University iLabs Project Team, hereafter referred to as iLabs@MAK. The procedures followed to develop Online Laboratories using the National Instruments Educational Laboratory Virtual Instrumentation Suite (NI ELVIS II™) platform is discussed. The laboratories were developed based on the Massachusetts Institute of Technology (MIT) iLabs Shared Architecture (ISA), a model that provides highly reliable generic services independent of the experiment domains. Modifications were made to the ELVIS version 1.0 code to introduce desired functionalities. Experiments were selected from three fundamental courses offered in the Department of Electrical Engineering, Faculty of Technology, Makerere University. Starting with the rationale for development of iLabs in specific courses, the paper presents the methods employed and the results obtained from the various experiments. Experiences and perceptions from over 300 students who performed the experiments were captured as a core aspect of the Research.
Keywords: Amplitude Modulation; Digital Logic; Frequency Modulation; iLabs; Pulse Code Modulation